Electrochemistry of silver nanoparticles - Toh, S (2015)
This thesis presents findings realising two main objectives. The first aim is to investigate the electrochemical detection of nanomaterials with an emphasis on silver nanoparticles. The second goal is to employ silver nanoparticles in electroanalysis to aid in the detection of other analytes. First, the detection of silver nanoparticles was demostrated through two different electrochemical methods, stripping voltammetry and 'nano-impacts'. For stripping voltammetry, the potential of metallic nanoparticles oxidation was quantified by various new analytical expressions for peak potential. For the novel method of 'nano-impacts', individual silver nanoparticles were successfully detected in an optically opaque suspension. Then, a comparison between the two techniques was achieved via the oxidation of silver nanoparticles with different capping agents. Strong capping agent effects was found for stripping voltammetry and one may markedly underestimate the amount of silver nanoparticle present on the electrode surface. The electrochemical sizing of nanoparticles via 'nano-impacts' remained unaffected by the capping agent effect. Amidst the study on the various types of capping agent, it was discovered that cetyltrimethylammonium bromide (CTAB) is electroactive due to the oxidation of its bromide content. This inspired the use of 'nano-impacts' to detect the presence of large CTAB micelles which self-assembled at concentrations above the critical micelle concentration. Next, various types of silver nanoparticles were applied to different electroanalytical systems to aid in the measurement of other analytes. (a) Small silver nuclei, remaining after the oxidative stripping of an electrode modified by silver nanoparticle suspension drop casting, allowed subsequent signal enhancement (at least a factor of three) in anodic stripping voltammetry of silver ions. (b) The thermodynamic favourable formation of silver halide complexes allowed the silver nanoparticle modified electrode to analyse the halide content of a solution. Hence, a proof-of-concept for an electrochemical sensor based on silver nanoparticle modified electrode for chloride ions was established. This might be applied to the pre-screening of cystic fibrosis, a genetic disease detrimental to many infants' lives. (c) Another key halide in human body, iodide ions, was also measured using a related concept. The level of iodide ions in synthetic human urine was determined. Last, the strong affinity of silver to thiol groups also warranted a study devoted to their interaction through electrochemical and spectroscopic measurements. It was found that there is no general mechanism for silver-thiol interaction and each thiol must be treated as a separate entity.